Comparative study of cleft palate dimension among east coast peninsular Malaysian and caucasian - Masudi, Sam'an Malik; Sulaiman, Nik Roslin Nik (Pusat Pengajian Sains Pergigian, Universiti Sains Malaysia, 2003)
The present study was conducted to con:tpare maxillary arch development of BCLP Kelantan Malay children with a BCLP caucasian children during the first four years of life and to give a detailed . description of maxillary arch development in Kelantan Malay children with a Bilateral Cleft Up and Plate (BCLP). Samples used in this study consist of seventy six non operated complete bilateral cleft lip and palate (BCLP) children, who were born between 1986 to 2000 and their dental casts were collected from Kota Bharu Hospital and USM Hospital. They were all of Malaysian Malay origin and had no other congenital anomaly other than oral cleft. The data of caucasian BCLP patient were collected fro~ dental casts at the University Hospital of Nijmcgen, Holland (PhD Degree Dissertation in. Medical Science of the University of Nijmegen, Netherland). Twenty six children. with complete bilateral cleft lip and palate were studied. They were born between 1976 and 1990. They were all of caucasian Dutch origin and had no other congenital anomaly than oral cleft. The inclusion criteria of the samples v.1ere CLP without other congenital abnormality and the exclusion criteria were CLP with other congenital abnormality as well as no present of soft tissue bridges. Dental impressions were taken from all samples and dental casts were made and the points were determined. Maxillary arch dimensions were calculated twice on the dental casts by using Digital Sliding Caliper (Fowler Ultra-Gold, USA). Digital sliding caliper can be connected to the computer by using Fowler digital connector and special data software. Measurement data were transfered to the computer and can be read on the monitor. Measurement of the anatomical and constructed points is determined according to Sillman and Robertson, where C-C' were intercanine width or, maxillary anterior arch width; T-T' were intertuberosity width or maxillary posterior arch width and IPrZ were total arch depth. Maxillary arch dimensions, were calculated fromthe coordinates and were converted into 12 different ·ages by interpolating ·data from birth to 48 months. The distance of the interpolated value to the nearest age period was not allowed to be m·ore than two weeks in the first. year of life and six weeks thereafter. In order to determine the measurement error from Kelantan control group, 76 dental casts, covering the full range of ages were randomly selected and digitized by same person similar to the method done to the Nijmegen group. To identify the differences betwen the BLCP Kelantan group and the BLCP Nijmegen group at the different ages, the Mann Whitney test and Student t-test was applied. As a coclusion we may state that during the first four years of life maxillary arch development in Kelantan children with a: complete bilateral cleft were different with a caucasian children with complete bilateral cleft. To be concluded that Kelantan BCLP group significantly have more severe cleft distance of the palate compared to Nijmegen BCLP group; and thus the Kelantan Malay children suffer more severe deft palate deformity.